Vztah mezi kvalitou zivota a BODE indexem u bývalých kuráků ve stabilní fázi chronické obstrukcní plicní nemoci - Koblízek, V; Salajka, F; Cermáková, E; Tomsová, M; Pohnetalová, D; Papousek, P; Bartos, V; Dobesová, T; Paráková, Z; Ruta, J; Sedlák, V (Vnitrni lekarstvi, 2009)
BACKGROUND AND AIM: This study was carried out to assess relationship between quality of life (QoL) and disease severity expressed by multifactorial prognostic index (BODE) in ex-smokers suffering from chronic obstructive pulmonary disease (COPD), minimally 8 weeks free of exacerbation. MATERIALS AND METHODS: The evaluation was performed in 98 randomly recruited COPD patients enrolled into a cross-sectional, observational CILIARY study at the Department of Pneumology, Charles University, Faculty of Medicine in Hradec Králové. In them, quality of life evaluation using the SGRQ questionnaire and the BODE index calculation was performed. We statistically compared interrelationship between BODE and COPD stages, SGRQ and COPD stages and interrelation of BODE and SGRQ. RESULTS: We found significant differences in QoL of COPD patients and QoL in group of healthy volunteers (p <0.001). Lower QoL and higher BODE score were associated with a higher stages of COPD (p < 0.001), with the exception non-significant difference in QoL (SGRQ score) and BODE index between stages I and II. Our study found positive correlation between the all SGRQ scores and multidimensional prognostic BODE index (r = 0.431-0.704). The strongest correlation (r = 0.704) was evident in activity domain of SGRQ. CONCLUSION: Our results proved close correlation ofquality of life (SGRQ) and multidimensional prognostic score (BODE) in stable COPD exsmokers' population. Both these scoring systems are useful tools for the assessment of clinical course and stratification of severity of COPD. However at present both scales are minimally used in the Czech Republic.
Keywords: senioři; Prognosis; Forced Expiratory Volume; Dyspnea; Middle Aged; průzkumy a dotazníky; mužské pohlaví; Pulmonary Disease, Chronic Obstructive; kvalita života; chronická obstrukční plicní nemoc; Smoking Cessation; ženské pohlaví; prognóza; Humans; Surveys and Questionnaires; lidé středního věku; dyspnoe; usilovný výdechový objem; Female; Aged; Quality of Life; odvykání kouření; lidé; Male